Creation of bimodal porous copper materials by an annealing-electrochemical dealloying approach. (10th May 2015) - Song, T.; Yan, M.; Shi, Z.; Atrens, A.; Qian, M.
Graphical abstract: Highlights: Bulk bimodal porous Cu materials with micro- and nano-sized pores were fabricated. The proposed annealing-electrochemical dealloying approach proved to be efficient. Annealing allowed redesign of the precursor alloy for anticipated dealloying. Annealing enabled more flexible dealloying in producing fine nanoporous structures. Abstract: Hierarchical (bimodal) porous copper (Cu) materials with micro- and nano-sized pores are desired for a wide variety of important applications. This study proposes an annealing-electrochemical dealloying approach for the creation of bulk bimodal porous Cu materials from an as-cast hypereutectic Al75 Cu25 (at.%) precursor alloy, which consists of pre-eutectic CuAl2 and lamellar eutectic α-Al(Cu)-CuAl2 . Annealing of the precursor alloy plays a critical role in the subsequent electrochemical dealloying for the creation of bimodal porous Cu. It decouples the lamellar eutectic structure and substantially increases the size of the α-Al(Cu) phase which determines the size of the subsequently produced micropores. In addition, it reduces the solubility of Cu in α-Al(Cu) and noticeably decreases the critical potential of the Al75 Cu25 alloy thereby enabling more flexible electrochemical dealloying. A variety of bimodal porous Cu structures were produced using the proposed approach. The most homogeneous bimodal porous Cu structure with the average ligament width of 52 nm was produced by electrochemical dealloying of the annealed Al75 Cu25 alloy at the applied potential of -0.5 V, which is above the critical potential of the α-Al(Cu) but below that of the CuAl2 phase. The influence of annealing on the microstructure and the subsequent electrochemical dealloying behaviours of the Al75 Cu25 alloy was characterised and discussed in detail.